Detecting endogenous SUMO targets in mammalian cells and tissues - Becker, Janina; Barysch, Sina-Victoria; Karaca, Samir; Dittner, Claudia; Hsiao, He-Hsuan; Berriel Diaz, Mauricio; Herzig, Stephan; Urlaub, Henning; Melchior, Frauke (Nature structural & molecular biology, 2013)
SUMOylation is a dynamic protein post-translational modification that regulates many eukaryotic proteins. Now a methodology using commercially available monoclonal antibodies coupled to MS analysis leads to the enrichment and identification of endogenous targets for SUMO1 and for SUMO2/3 in HeLa cells and mouse liver. This protocol can be adapted for other tissues and organs.